Optimal Distinctive Open Innovation as Antesedent and Consequences of Innovative Work Behavior - Luhgiatno Luhgiatno; Emiliana Sri Pudjiarti (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2020)
The main objective of this study is to explain of the effect of the concept of optimal distinctive open innovation as mediation in relation to Person-Job Fit and employee engagement on innovation work behavior. The research uses quantitative methods with primary data and lecturers from private universities as the object of research. Data were collected using google form facility with a sample size of 190 lecturers. Measurement of variables using a likert scale of 1 to 7. Through structural equation modeling analysis it was concluded that the mediating effect on the hypothesized relationship was statistically significant. Thus the success-oriented way of thinking requires the expertise of employees to always create creative, superior and unique ideas. Higher Education must always pay attention to the principles of industrial management and professionalism in human resource management, in order to survive and develop. Superior skills produce superior performance, and superior skills are distinctiveness competences which are one of the assets for organizations to achieve positive advantages. The company's positional advantage is expressed by performance outcomes which include customer satisfaction and loyalty